Molecular Phylogeny of the Genus Nipponnemertes (Nemertea: Monostilifera: Cratenemertidae) and Descriptions of 10 New Species, With Notes on Small Body Size in a Newly Discovered Clade - Hookabe, Natsumi; Kajihara, Hiroshi; Chernyshev, Alexei V.; Jimi, Naoto; Hasegawa, Naohiro; Kohtsuka, Hisanori; Okanishi, Masanori; Tani, Kenichiro; Fujiwara, Yoshihiro; Tsuchida, Shinji; Ueshima, Rei (Frontiers in Marine Science, 2022)
Nemerteans, or ribbon worms, have been reported from intertidal to hadal depths, often showing bathymetrically wide distribution in genus levels. Although current nemertean systematics practices require to provide DNA sequences and infer phylogenetic relationships with suitable molecular markers, previous molecular systematics on nemerteans are mostly biased toward shallow-water species. Members in the genus Nipponnemertes occur worldwide, from tropical to polar waters and intertidal to bathyal waters. Molecular phylogenetic studies are scarce for the genus; only six shallow-water species of 18 species in the genus were subject to molecular phylogeny. Thus, Nipponnemertes is one candidate that needs to be assessed by genetic approaches. In this study, we performed molecular phylogenetic analyses using 59 specimens in 23 species based on partial sequences of two mitochondrial (16S rRNA and cytochrome c oxidase subunit I) and three nuclear gene markers (18S rRNA, 28S rRNA, and histone H3). Our extensive sampling from intertidal to bathyal waters in the Northwest Pacific significantly updated the fauna of Nipponnemertes in this region from four to 17 species. We herein establish 10 new species and provide an updated species list concisely summarizing all the congeners known from the world. Our phylogenetic tree indicated three major lineages within the genus (herein referred to as “Clade A, B, and C”), each presumably characterized by the combination of morphological characters in the head region. Members in Clade A are: Nipponnemertes pulchra (Johnston, 1837), Nipponnemertes ogumai (Yamaoka, 1947), and several unidentified congeners, characterized by having demarcated head without cephalic patches; members in Clade B are: Nipponnemertes crypta sp. nov., Nipponnemertes jambio sp. nov., Nipponnemertes neonilae sp. nov., and Nipponnemertes ojimaorum sp. nov., species having demarcated head with cephalic patches; members in Clade C are: Nipponnemertes ganahai sp. nov., Nipponnemertes kozaensis sp. nov., Nipponnemertes lactea sp. nov., Nipponnemertes notoensis sp. nov., Nipponnemertes ornata sp. nov., Nipponnemertes sugashimaensis sp. nov., and two unidentified forms collected off Jogashima (Japan) and Guam (USA), species with non-demarcated head lacking cephalic patches. Furthermore, we discuss the evolution of remarkably small body size retained among Clade C.